2015
DOI: 10.1007/s00592-015-0813-1
|View full text |Cite
|
Sign up to set email alerts
|

The top 100 most cited scientific reports focused on diabetes research

Abstract: The online-only Data Supplement is available with this article at http://hyper.ahajournals.org/lookup/suppl/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…The number of citations for the 10 top‐cited articles in lithium toxicity varied from 211 to 79, which was less than those in other subspecialties in non‐toxicological fields and within the range of citations in other subspecialties in toxicological fields . Citations fluctuate in different subspecialties and depend on the research activity in certain field.…”
Section: Discussionmentioning
confidence: 97%
“…The number of citations for the 10 top‐cited articles in lithium toxicity varied from 211 to 79, which was less than those in other subspecialties in non‐toxicological fields and within the range of citations in other subspecialties in toxicological fields . Citations fluctuate in different subspecialties and depend on the research activity in certain field.…”
Section: Discussionmentioning
confidence: 97%
“…This trend of US dominance in medical research was also found in other fields such as general surgery,39 anaesthesia,40 cardiology41 and diabetes 42. Part of the reason for this is due to the USA having large and pluralistic government funding, high academic quality and a heritage of academic infrastructure that is conducive for research in multidisciplinary fields 43.…”
Section: Discussionmentioning
confidence: 87%
“…With a historical perspective on the past 50 years, we open this first issue of 2016 with a report on the 100 most cited papers of all times in the field of diabetes research [2]. Though not revealing major surprises, the report confirms that randomized controlled clinical trials, headed by the DCCT and UKPDS, and position statements/guidelines, remain most popular among research workers.…”
mentioning
confidence: 86%